Anos Iniciais da Escolarização e Relações de Gênero: representações de docentes sobre gênero - Lusa, Diana (2010)
The main objective of this study was to analyze what speeches, teaching practices and interactions between the teacher(she/he) and students (she/he) have shown about gender relations. To take into account this larger goal, some questions were created in order to guide the study such as, which are the teacher s representations about boys and girls, men and women?; what do the classroom say, and how it is organized about the relationships that may be on this place?; How are treated femininities and masculinities on teacher s practices? what kind of work are developed in the classroom?, how do the teachers speak to the girls and the boys? The theoretical framework to support the analysis of field data has a brief review on feminist social theory from among others, Joan Scott, Guacira Louro e Maria Custódia da Rocha. There is also a reflection on education and gender, that it seeks to elucidate which concept of gender is used in some ways and also the relationship of this concept to teaching, when it takes a bit from the history of teaching and the process of feminization of teaching. It is also made a reflection about how school differences have been built and it is shown how some academic work which had as its study object gender in school . Besides what had been exposed, on the theoretical concepts are considered some of the cultural studies, such as identity and representation, about how we create ourselves and how we are being created (male and female) as social human beings from the representations we have and which has the world around us. It has been made an analysis with the theoretical and field data mentioned on the teacher s practices and what they said about gender relations, which is located in chapter six of this work. It was possible to see three teachers and three different ways of dealing with situations of conflict or gender inequality that appear in their classrooms. Three ways to understand being a man and being a woman , being a boy and being a girl . Teachers who struggle to demystify truths about gender, although that reflects in a different way similar representations about the place of men and women, especially in teaching, even if they do not agree with these social and cultural definitions. What we realized from this research is that even if the subjects are aware of gender issues there is some representation that teaching is a female occupation, even if this / these teachers are opposed to it. On the representation of boys and girls I did not notice differences in how these female teachers and this male teacher face boys and girls with respect to performance. When it comes to behavior subject it has some changes. It is believed that this study will contribute for further reflection on gender relations, particularly in schools, where this kind of study does not happen frequently. We hope to contribute to the academic and school environment with a more empirical study, which is not easy to find.